Eff ect of the sub-chronic administration of some commonly used herbal products on the liver enzymes, body weight, and feed intake of albino Wistar rats: Any implication for public health? - N. B. Egenti, J. C. Enye, H. N. Chineke, Prosper O. U. Adogu (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The present study was focused to assess the effects of the administration of commonly used herbal products viz.: Yoyo cleansing bitters, T. angelica herbal tonic, and Bio-Strath elixir on the liver enzymes, body weight, and feed intake in adult albino Wistar rats. A total number of seventy Wistar rats were divided into three major groups. Each group received a particular herbal product and each of these groups was further subdivided into subgroups that received various dosages of each of the herbal products. The rats were acclimatized for 14 days after which they received different doses of each of the herbal products for 6 weeks. The body weight, feed intake, and modulation in liver enzymes were evaluated. The feed intake and body weights were reduced in animals that received T. angelica herbal tonic and Yoyo cleansing bitters at twice the normal dose once and twice daily, but the reverse was the case for the rats that received Bio-Strath elixir even at higher doses. The liver enzymes were increased at all doses in rats which were given Bio-Strath elixir but it was not significant (P > 0.05), while those of Yoyo bitters and T. angelica herbal tonic were significantly increased (P < 0.05), especially at higher doses. From our study results it was suggested that a higher dose than the manufacturer’s recommended dose taken for a longer duration can elevate liver enzyme, thus causing abnormal liver function.